A Historical Review of Postponement Research. Issue 1 (1st June 2019) - Zinn, Walter
Abstract : This historical review traces the development of postponement research starting in the fifties. The focus is on seven related themes: connecting form and time postponement, conceptual extensions to postponement, decoupling points, design for postponement, customization and mass customization, factors favoring postponement implementation, and postponement in global settings. Within these themes, the review includes concepts such as postponement costs, decoupling points, part commonality, and the impact of demand correlations on the benefits of postponement. The review suggests that substantial progress has been made in postponement research.